Experience in upgrading the traverse of the paint chamber10.22281/2413-9920-2020-06-02-301-310 - Prusov A.Yu.; Melnikov A.N. (Научно-технический вестник Брянского государственного университета)
Traverses are a separate group of General classification of load-grabbing devices used by lifting machines to work with all kinds of goods. Structurally, they represent a linear or spatial (frame) metal structure with various additional elements (branches, grips). Thanks to the traverses, it is possible to eliminate the occurrence of compressive (squeezing) forces of loads, reduce the lifting speed of the hook of the lifting mechanism and reduce the time of the lifting operation. The article presents a brief analysis of existing traverse designs and methods of their calculations. The problem of designing a spatial traverse for use in the painting chamber of a machine-building enterprise is described. A practical example of cargo hanging on a symmetrical traverse is considered as a mandatory element of the technological operation. The necessity of applying the requirements of «safety culture» for all stages of lifting operation is emphasized. The necessity of preliminary preparation of design and operational documentation in connection with the technological features and capabilities of a particular production is indicated. A positive result has been achieved in the implementation of the design of the frame traverse for the painting chamber in conjunction with the safe working methods reflected in the product data sheet and in the operation manual. The conclusions focus on the need to expand the experience to other types and types of traverse, as well as the need for systematization and generalization of the experience, the accumulation of statistical data.